(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In this paper I try to explain a number of lexical as well as morphological and phonetic aspects of the Celtic and non-Celtic dialects once spoken in the West of the Iberian Peninsula. The first chapter refers to the Lusitanian adjective IFADEM, that I reconstruct as *en-bhat-yom. Next I discuss the origin of the placename Glandomiro, which I would translate as ‘shore of the Mira (river)’ and which is related to the Lusitanian godnames OCRIMIRAE and REVE REVMIRAEGO. Afterwards I discover a hitherto undetected Celtic placename *Coirobriga. Last I discuss the Celtic personal name CINTVMVNIS, which I trace back to Pcelt. *kintúsamos.